Prescription Patterns of Evidence-Based Heart Failure Medications in a Tertiary Hospital in North-Western Nigeria—A Retrospective Study - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Several large clinical trials on the use of medical therapy in the management of heart failure have shown angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs), beta blockers (BBs), and mineralocorticoid receptor antagonists (MRAs) to be of proven benefit and are recommended by guidelines.Aim:The aim of this study is to describe the trend of prescription and dosing of evidence-based medications used for chronic heart failure (CHF) in our population.Settings and Design:This is a retrospective study on the pattern of prescription of evidence-based heart failure medications on 200 consecutive patients with CHF who attended the cardiology clinic or were admitted into the Medical wards from January 2020 to December 2020 at Murtala Muhammed Specialist Hospital, Kano, North-Western Nigeria. The data was obtained from patients' records.Statistical Analytics Used:Data obtained were analyzed using Statistical Package for Social Sciences (SPSS) version 23 software. (SPSS Inc. Illinois, USA).Results:ACE inhibitors or ARBs were prescribed in 89 (44.5%), BBs in 76 (38%), and MRAs, in 192 (96%). None of the patients were prescribed angiotensin receptor-neprilysin inhibitors (ARNi) or sodium-glucose cotransporter-2 inhibitors (SGLT2 inhibitors).Conclusion:Evidence-based heart failure medications are underutilized in patients with CHF in our population. Improved uptake and up-titration are needed for better patients' outcomes.